EFFECT OF NANO-SILICA ADDITION ON PHYSICO-MECHANICAL PROPERTIES AND DURABILITY OF CONCRETE - Adnan Mujkanovic; Anesa Bitić; Marina Jovanović; Nevzet Merdić; Amel Zahirović; Amna Karić (Journal of Sustainable Technologies and Materials, 2022)
This paper presents the results of an experimental investigation into the effect of nano-silica addition on the mechanical properties and durability of concrete. Three mixes of concrete containing 0%, 2%, and 4% nano-silica by weight of cement were tested. The slump of fresh concrete as well as compressive strength, dynamic modulus of elasticity at 2, 7, 28, 90, and 180 days, and flexural strength at 2, 28, and 90 days of hardened concrete were determined. As for indicators of concrete durability, the total volume of permeable voids, water absorption, the rate of water absorption, and the freezethaw scaling resistance were determined. Test results showed that the incorporation of nano-silica in concrete resulted in an improvement of all mechanical properties of concrete, as well as concrete durability parameters that are tested.